2021
DOI: 10.1136/rmdopen-2020-001235
|View full text |Cite
|
Sign up to set email alerts
|

Risk for infections with glucocorticoids and DMARDs in patients with rheumatoid arthritis

Abstract: Immunomodulatory therapy for rheumatoid arthritis (RA) carries risk for infectious complications. Understanding the risks of different therapeutic options is essential for making treatment decisions and appropriately monitoring patients. This review examines data on the risks for serious infections and other key infections of interest for the major classes of agents in use for RA: glucocorticoids, conventional synthetic disease-modifying antirheumatic drugs (DMARDs), biologics and Janus kinase (JAK) inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
3
17
0
2
Order By: Relevance
“…Patients with RA are known to be at risk for developing HZ, including ophthalmic HZ and post-herpetic neuralgia [ 117 ]. Clinical experience has shown that this baseline risk is enhanced by drugs such as JAK inhibitors (mostly tofacitinib), TNFis, and IL-6Ris (mostly infliximab), especially when used in combination with GCs or in patients with co-morbidities or 50 years of age or older [ 118 ]. The mechanisms underlying the increased risk of VZV reactivation in these patients are unclear, but a possible explanation is that the drugs interfere with the onset and persistence of VZV-specific memory T-cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA are known to be at risk for developing HZ, including ophthalmic HZ and post-herpetic neuralgia [ 117 ]. Clinical experience has shown that this baseline risk is enhanced by drugs such as JAK inhibitors (mostly tofacitinib), TNFis, and IL-6Ris (mostly infliximab), especially when used in combination with GCs or in patients with co-morbidities or 50 years of age or older [ 118 ]. The mechanisms underlying the increased risk of VZV reactivation in these patients are unclear, but a possible explanation is that the drugs interfere with the onset and persistence of VZV-specific memory T-cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a US nationwide analysis, infection was the most common complication of spine surgery (18) and was the leading cause of readmission after cervical fusion surgery in patients with RA (43). Among DMARDs, biologics, JAK inhibitors and high doses of glucocorticoids have been associated with an increased risk of infections (44,45). However, con icting results of biological DMARDs, mainly tumour necrosis factor antagonists, have been reported in many studies, including both increased and unchanged risks of superimposed infections after surgery (46).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the thiourea was confirmed with the appearance of a clear downfield signal for the (C=S) in the carbon NMR spectra at around 181 ppm. Moreover, the methylene (-CH2-) bridge available in compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) was observed in the proton NMR spectra as two protons appearing in the range of 4.37-4.95 ppm. We decided to explore the effect of diverse benzyl substitutions on the NF-κB and EGFR inhibitory activity.…”
Section: Chemistrymentioning
confidence: 99%
“…The commonly prescribed anti-inflammatory drugs have potentially serious side effects: NSAIDs are known for their potential to induce gastrointestinal ulceration and bleeding [ 5 ]. Many antirheumatic drugs, such as methotrexate, sulfasalazine, and hydroxychloroquine, may cause an increased risk of infection and hepatotoxicity [ 6 , 7 ]. Anti-inflammatory glucocorticoids are effective, but the therapy has metabolic and cardiovascular side effects, and long-term treatment is limited due to the development of resistance [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%